Synthesis of new indanyl nucleoside analogues and their biological evaluation on hepatitis C virus (HCV) replicon - Gómez Elías, Matías Daniel (2019)
Here, we report a convenient synthetic procedure for the preparation of four novel indanyl carbanucleoside derivatives in the racemic form. The action of these compounds against hepatitis C virus was evaluated in vitro using the replicon cell line, Huh7.5 SG. Contrary to our expectations, all these compounds did not inhibit, but rather promoted HCV genotype 1b (HCVg1b) replication. Similar effects have been reported for morphine in the replicon cell lines, Huh7 and Huh8. Several biological experiments and computational studies were performed to elucidate the effect of these compounds on HCVg1b replication. Based on all the experiments performed, we propose that the increase in HCVg1b replication could be mediated, at least in part, by a similar mechanism to that of morphine on the enhancement of this replication. The presence of opioid receptors in Huh7.5 SG cells was indirectly determined for the first time in this work.